Perbaikan Kualitas Daya Menggunakan D-STATCOM pada Sistem Distirbusi Tegangan Rendah - Ceri Ahendyarti; Wahyuni Martiningsih; Anggoro Suryo Pramudyo (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2021)
This study explains of disturbances in the low voltage distribution system. The disturbance that often occurs in such a system is a single phase to ground fault. One of the most common disturbances in the quality of electrical power is voltage sag. These disturbances can be minimized or corrected by using D-STATCOM compensation. In this study, D-STATCOM is used to compensate for the voltage drop (voltage sag) due to short circuit faults. The components of D-STATCOM used in this research are IGBT, DC battery, filter, and controller with the working principle according to Park transformation. The simulation results of this study showed that the voltage sag increased up to 96%. Based on the results obtained, it can be said that the performance of D-STATCOM is quite good in compensating for voltage drops due to interference.